A Survey of Current Practice for Antibody‐Mediated Rejection in Heart Transplantation. Issue 4 (15th February 2013) - Chih, S.; Tinckam, K. J.; Ross, H. J.
<x xml:space="preserve">Abstract</x> No evidence based management guidelines exist for antibody mediated rejection (AMR) in heart transplantation. The International Society for Heart and Lung Transplantation (ISHLT) recently introduced standardized pathologic based diagnostic criteria for AMR (pAMR 0–3). We evaluated international practice for the management of AMR focusing on pAMR grade, donor specific antibody (DSA) and allograft function. On‐line survey data were analyzed from 184 ISHLT members (physicians‐78%, surgeons‐20%). The majority were from adult‐transplant (84%), medium‐large volume centres (transplants/year: 10–25, 61%; 25–50, 19%) across North America (60%) and Europe (26%). Irrespective of pAMR grade and DSA, 83–90% treated a drop in ejection fraction (EF ≤45% or >25% decrease). In the presence of stable EF, an increasing number elected treatment for progressively severe pAMR grade (p < 0.001) and for accompanying DSA (p < 0.05, pAMR 1–3). Intravenous steroid was the most commonly used therapy followed by intravenous immunoglobulin (IVIG) or plasmapheresis, rituximab and thymoglobulin. Plasmapheresis and rituximab were favored for positive versus negative DSA (p < 0.05). Using a threshold of ≥70% consensus among respondents, treatment for AMR may be considered for a drop in EF, asymptomatic pAMR 3 or asymptomatic pAMR 2 with DSA. Combination steroid, IVIG and plasmapheresis are suggested as initial therapies.